Structural Analysis of Success Factors of Small Medium Business (Ukm) Using Interpretative Structural Modeling (ISM) Approach In Bungaraya Sub-District - Rahmi, Auliya (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
The aims of this research were: 1) to know the structural modeling to know the priorities (key factors) and supporting factors in the success factors of a UKM, 2) to know the solutions that can be suggested when the key success factors for UKM are known. The design of this study is qualitative research in the form of expert opinion that has had successful SMEs. The research began with interviews and giving questionnaires to representatives of each UKM, the number of UKM studied in this study was 4, so the total number of experts interviewed and given questionnaires were also 4 people. SMEs that contributed to this research was in the culinary field. The name of the UKM is Sate Pariaman, RM. Surabaya, My Mama's Kitchen 3B, and Ipat restaurant. Where is this study, using expert judgment using the VAXO questionnaire in collecting data? In data processing in this software, researchers use EXIMPRO – ISM.exe software. Based on the results of the structure, it can be seen in order of sub-elements with the highest ranking, namely Market Demand (E11) as the key factor influencing the success of SMEs. Then the second rank is Own Capital (E5), and the third rank has 21 elements namely Motivation (E1), Formal Education Level (E2), Experience (E3), Entrepreneurial Spirit and Leadership (E4), Loan Capital (E6), Profit Level and Capital Accumulation (E7), Financial Governance (E8), Production Capacity (E9), Modern Technology and Quality Control (E10), Technology Selection (E12), Market Demand (E13), Competitive Pricing (E14), Promotion (E15 ), Distribution Channels and Marketing Areas (E16), Business and Investment Climate (E17), Lots of Competition in the Same Field (E18), Economic Growth (E19), Community Income Level (E20), Capital Assistance from Related Institutions (E22), There is Technical Guidance (23), Monitored and Evaluation (E24). The last ranking is Government Policy (E21).